Microelectrode Arrays and Microfabricated Devices in Electrochemical Stripping Analysis - Beni, V.; Arrigan, Damien (Bentham Science Publishers Ltd., 2008)
In this article a comprehensive overview of the development in the field of electrochemical stripping analysis with microelectrode arrays and microfabricated devices is presented. Due to the vastness of topic, this mini-review deals only with the use of regular microelectrode arrays. After the description of the main fabrication methodologies employed, a large part of the review is dedicated to applications, categorised by the electrode material. Microelectrode arrays have found application in several areas of electroanalytical science including clinical and environmental analysis. They have been used for detection of heavy metals in waters, soil extracts and blood, proving to be reliable analytical devices and bringing the advantages of low-cost, simplicity of use and easy adaptability to field measurement. In many applications, limits of detection are sub-part per billion. Finally a short section of the review discusses miniaturised potentionstats